Health Status and Functional Abilities of Elderly Males Visiting Primary Health-care Centers in Khamis Mushait, Saudi Arabia - Al-Qahtani AM (Dove Medical Press, 2020)
Awad Mohammed Al-Qahtani Department of Family and Community Medicine, College of Medicine, Najran University, Najran, Saudi ArabiaCorrespondence: Awad Mohammed Al-QahtaniDepartment of Family and Community Medicine, College of Medicine, Najran University, PO Box: 1988, King Abdulaziz Road, Najran 55461, Saudi ArabiaTel +966-17 7930 6344Email awadresearch17@gmail.comBackground: There is an aging population all over the world, and Saudi Arabia is no exception to it. An aging population poses several challenges to the health-care sector.Aim: The aim of this study was to examine the health status and functional abilities of elderly people visiting primary health-care centers in Khamis Mushait, Saudi Arabia.Methods: This cross-sectional study involved elderly male Saudi nationals aged 60 years and above. Self-rated health status and body pain, functional status, geriatric review of systems and other relevant data were collected using the Geriatric Health Questionnaire of University of Iowa Health Care. All statistical analyses were performed using SPSS version 21.Results: The study results showed that the overall health of the elderly was either good (32.9%) or very good (32.3%), while 14.2% rated their health as excellent. Only two participants rated their health as poor. The majority of the participants (71.9%) had no functional impairment in basic activities of daily living (BADL), while 35.7% had mild impairment in instrumental activities of daily living (IADL). Only two participants were found to have total impairment in IADL. The most common limitation among BADL was walking (21.1%) and among IADL was doing the housework. The notable factors associated with functional impairment in BADL and IADL were old age (≥ 80 years), poor eyesight, memory impairment, having trouble with control of bladder, falls twice or more, taking more than two medications, being sexually inactive, poor self-rated general health and severe self-rated body pain (all P< 0.05) among others.Conclusion: The majority of the elderly were able to perform BADL independently and to a lesser extent IADL; the overall self-rated general health was found to be good. Further research in the field of geriatrics is warranted to plan better, and design public health policies and provide efficient care to elderly patients.Keywords: elderly, activities of daily living, ADL, health status, Saudi Arabia